“Valoración socio-ambiental de los componentes de las unidades del paisaje en el páramo Leyvisa – Panzarumi, provincia de Cotopaxi, propuesta de conservación” - Peralvo Casillas, Norma Gabriela (2023)
The present study allowed the socioenvironmental assessment of the components of the landscape units in the Páramo Leyvisa - Panzarumi. This place is located 24 km from Salcedo, presenting an area of ​​50.7 hectares, which unfolds in the upper eastern part of the canton, housing an ecosystem of humid Andean forest and páramo grasslands. The proposed objectives demonstrated the current conditions of the socio-environmental components that make up the units of the natural landscape; evaluating the quality, fragility and visual absorption capacity; and, finally, I elaborated a conservation proposal for this important natural area. The methodology that was reduced was through the BLM method, the same one that allows analyzing the visual quality and evaluating the basic characteristics of the landscape components, through the weighting of attributed values. The results obtained from the application of the survey determined that the visual quality in the Páramo Leyvisa-Panzarumi is in a moderate range of (12 to 18 points), due to a high anthropic incidence and areas with varied features in shape, color , line and texture, which were common in the studied region.